Influence of Internal Audit, Information & Communication, and Monitoring of Internal Control Performance - Ery Herliana; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2023)
Weak internal controls can cause fraud in the organization or company. This causes need for internal control performance which is influenced by several factors to minimize the risk of loss by fraud. This research is aim to know the effect of internal audit, information & communication, and monitoring on internal control performance. The research method used a qualitative method and literature review or library research. The results of this literature review article are: 1) Internal audit has an effect on internal control performance; 2) Information & communication affects the performance of internal control; and 3) Monitoring affects the performance of internal control.